Dzieje współpracy Bydgoszczy z miastami partnerskimi po 1989 roku (Kronika Bydgoska, 2013)
Partner cities are a special and very popular type of international co-operation of the local authorities. The specificity of this co-operation results first of all from its informal character and direct involvement of so-called ordinary people - residents of cities. This article presents co-operation based on partnership conducted by self-government of Bydgoszcz after the year 1989. After the initiation of political transformation, especially the reinstatement of territorial self-governments in Poland, foreign contacts of cities became more authentic. Besides already existing contacts with cities from the former socialist block (Cherkasky, Kragujevac), efforts were made to co-operate with many European, North American ans Asian cities: Wilhelmshaven and Mannheim (Germany), Perth (Scotland), Hartford (USA), Ningbo (China), Pavlodar (Kazakhstan), Pitesti (Romania), Patras (Greece), and Kremenchuck (Ukraine). Cultural exchange with Reggio Emilia (Italy) was continued. The most important areas of international twin co-operation of the city on the Brda River include first of all exchange of young people, organization of different types of cultural and sports events, leveraging EU funds for joint undertakings, sharing experiences in the scope of self-government activity, and economic co-operation. The author shows the genesis, circumstances of establishment and development of contacts between Bydgoszcz and its foreign partners, as well as examples of real benefits resulting from them. Owing to both the number of established contacts, their broad geography, and the diversity of forms and ways of conducted co-operation, one can say that the self-government of Bydgoszcz has gained adequate experience and applies properly the idea of twin cities.